(untitled) - Barbe, Walter B. (New York, 1999)
Each level unit provides a sequential Reading Skills Checklist of the skills to be mastered at that grade/reading level for easy individual record keeping, plus 40-70 short, reproducible informal Reading Skills Competency Tests for measuring students' mastery of each skill on the Checklist at that level. Each also includes a Group Summary Profile for recording class progress and a separately printed wall chart that maps out the entire reading skills progression from Readiness through Advanced levels
Keywords: Reading skills competency tests,Reading; Ability testing